ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI BELANJA MODAL KABUPATEN/KOTA DI PROVINSI JAWA TENGAH 2014-2016 - Athina Novi Hapsari, 14.05.52.0084; Maryono, Maryono (Students' Journal of Accounting and Banking, 2018)
This study aims to analyze the effect of Local Government Revenue, General Allocation Funds, Special Allocation Funds and Economic Growth of Capital Expenditures in the District / City in Central Java Province 2014-2016. Economic growth in this study is proxied with Gross Regional Domestic Product. Population in this research is all District and City in Central Java Province. The sample of this research are 35 regencies and cities in Central Java Province with period 2014-2016. This research data in the form of secondary data in the form of Realization Report of APBD and table of Gross Regional Domestic Product of Central Java Province. The method of analysis used in this study is multiple linear regression. Based on the results of the study can be concluded that the Local Government Revenue , General Allocation Fund and Special Allocation Funds has a significant positive effect to Capital Expenditures. Economic Growth does not significant negative effect on Capital Expenditure. Keyword : Local Government Revenue, General Allocation Funds, Special Allocation Funds , Economic Growth and Capital Expenditures